KOMUNIKASI INSTRUKSIONAL DALAM MENANAMKAN NILAI-NILAI AL QURAN KEPADA JAMAAH MAJELIS TAFSIR AL QURAN DESA LAUT DENDANG KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG - Muhammad Alfi Syahri (Al-Balagh : Jurnal Komunikasi Islam, 2017)
Abstrak: The purpose of this study are: 1. Instructional communication in embed values of theQuran to pilgrims interpretation council of Al-qur’an at Laut Dendang Village Sub District Of PercutSei Tuan, District Deli Serdang. 2. To discover the instructional communication media in embed thevalues of the Qur’an to the pilgrims interpretation councilof Al Quran at Laut Dendang Village SubDistrict Of Percut Sei Tuan, District Deli Serdang. 3. To find out the instructional communicationbarriers in embedthe values of the Qur’an to the pilgrims interpretation council of Al Quran at LautDendang Village Sub District Of Percut Sei Tuan, District Deli Serdang4. To knowing the implicationsfor instructional communication in embedthe values of the Qur’an to the pilgrims interpretationcouncil of Al Quran at Laut Dendang Village Sub District Of Percut Sei Tuan, District Deli Serdang.This research are using field research with qualitative methods. Data collection techniques that usedin this study are interviews, observation, and documentation. Data were collected and analyzed,afterwards be concluded in a descriptive way. Source of the data found is the source of primary dataand secondary data sources. Data collection tool was interview, observation, and documentation.